Haemosporidian infections and host behavioural variation: a case study on wild-caught nightingales (Luscinia megarhynchos). Issue 2 (4th March 2017) - Marinov, M.P.; Zehtindjiev, P.; Dimitrov, D.; Ilieva, M.; Bobeva, A.; Marchetti, C.
Abstract : Haemosporidians (protozoan blood parasites) are known to modify avian hosts' behaviour in the acute phase but not much is known about the chronic phase. We identified blood parasites by microscopy and a polymerase chain reaction (PCR)-based method in a sample of 22 wild-caught nightingales ( Luscinia megarhynchos ) in northeast Bulgaria. We compared non-infected and infected birds in single behavioural traits under the hypothesis that infected birds should show more risk-taking behaviours and quicker exploration. Infected nightingales were more prone to risk-taking and this behavioural trait was significantly correlated with the intensity of infection. However, no differences were found in exploration speed or body condition and reactions to a stressful situation (weight change in captivity, handling), which might be due to either a lack of differences or the limited sample size.